2010
DOI: 10.1177/147470491000800108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Guilt

Abstract: The recent emphasis on humans as cooperative breeders invites new research on human family dynamics. In this paper we look at maternal guilt as a consequence of conditional maternal investment. Solicited texts written by Finnish mothers with under school-aged children in 2007 (n = 63) described maternal emotions perceived as difficult and forbidden. Content analysis of guilt-inducing situations showed that guilt arose from diverging interest and negotiations between the mother and child (i.e., classic parent-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 35 publications
3
46
0
1
Order By: Relevance
“…This difference may be a result of high expectations for mothers (Thurer, 1995; Hays, 2003; Johnston and Swanson, 2006): a strong focus on women’s careers may bring about feelings of guilt and hence push aspirations for their mother identity, while a stronger focus on family does not bring about the same guilt for their work identity and thus does not push career identity (Rotkirch and Janhunen, 2010; Liss et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…This difference may be a result of high expectations for mothers (Thurer, 1995; Hays, 2003; Johnston and Swanson, 2006): a strong focus on women’s careers may bring about feelings of guilt and hence push aspirations for their mother identity, while a stronger focus on family does not bring about the same guilt for their work identity and thus does not push career identity (Rotkirch and Janhunen, 2010; Liss et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…This difference may be a result of high expectations for mothers (Johnston & Swanson, ). A strong focus on women's careers may bring about feelings of guilt and hence push aspirations for their mother identity, while a stronger focus on family does not bring about the same guilt for their work identity and thus does not push career identity (Rotkirch & Janhunen, ). This means high career aspirations may make women more vulnerable to work–family conflict once they enter parenthood.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most therapists indicated that they focused on the mothers’ depression. Their guilt‐feelings, common in mothers with newborn infants (Rotkirch & Janhunen, ), also were addressed. These feelings could sometimes be linked to the new situation of having become a parent.…”
Section: Discussionmentioning
confidence: 99%